Gambaran Kematangan Sosial Pada Mahasiswa Dengan Orangtua Tunggal Pada Fakultas Kesehatan Masyarakat Undana - Marang, Mariana Servina W (Al Makki Publisher, 2025)
This study aims to describe the social maturity of students at the Faculty of Public Health, Nusa Cendana University (FKM Undana) who are raised by a single parent—specifically the mother—due to the death of the father. The subjects in this study are students aged 18–20 years who experienced the loss during their adolescent growth and development period. The research uses a descriptive qualitative approach with data collected through in-depth interviews and analyzed using thematic analysis. The results show that the level of social maturity among students raised by single mothers varies, influenced by the parenting style applied and the individuals’ ability to manage emotions and interact with others. Some participants demonstrated high levels of independence and responsibility, while others encountered difficulties in forming healthy social relationships. This study provides insight into the crucial role of single mothers’ parenting in shaping the social maturity of young adults.